2021
DOI: 10.9734/arjom/2021/v17i330283
|View full text |Cite
|
Sign up to set email alerts
|

Analytical Solution of a Non-isothermal Flow in Cylindrical Geometry

Abstract: This study proposes analytical solution to the problem of transport in a Newtonian fluid within a cylindrical domain. The flow is assumed to be dominated along the channel axis, and is taken to be axi-symmetric. No-slip boundary condition is considered for velocity while the temperature and concentration have Dirichlet boundary values. The resulting problem is transformed into a set of non-trivial variable coefficient differential equations in a cylindrical geometry. By adopting the series solution method of F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 11 publications
2
9
0
Order By: Relevance
“…It was observed that an increase in pressure gradient (steady or pulsatile) results in an increase in velocity profile of the fluid in a cylindrical channel. This is in agreement with Nwaigwe and Amadi [14].…”
Section: Fig 4 the Effect Of Injection Parameter On Concentration Pro...supporting
confidence: 93%
See 4 more Smart Citations
“…It was observed that an increase in pressure gradient (steady or pulsatile) results in an increase in velocity profile of the fluid in a cylindrical channel. This is in agreement with Nwaigwe and Amadi [14].…”
Section: Fig 4 the Effect Of Injection Parameter On Concentration Pro...supporting
confidence: 93%
“…This is because as the magnetic field increases, a Lorentz force is introduced and this inhibits the flow of the fluid. This is in line with Nwaigwe and Amadi [14], Omamoke and Amos [17], Bunonyo and Amos [16], Baoku et al [18]. Fig.…”
Section: Fig 4 the Effect Of Injection Parameter On Concentration Pro...supporting
confidence: 90%
See 3 more Smart Citations